Characterization and Phylogenetic Analysis of Soybean Rhizobial Strains from Java and Sumatra - SETIYO HADI WALUYO (Microbiology Indonesia, 2011)
Twenty-seven and twenty-four soybean rhizobial isolates from Java and Sumatra, respectively,were characterized. Based on cross-inoculation,  eight isolates from Java and nine from Sumatra could be grouped as soybean specific rhizobial species , while 19 isolates from Java and 15 from Sumatra were  promiscuous. ARDRA of intergenic spacer region of 16S-23S rDNA showed that the isolates from Java were different from those from Sumatra. Six soybean specific isolates from Java and one from Sumatra were in the same cluster with the reference strain, Bradyrhizobium japonicum USDA 110, thus could be classified as B. japonicum. One soybean specific isolate from Java’s has a distinct position, while the other soybean specific isolate from Java was placed in another group dominated by isolates from Sumatra. The nineteen promiscuous isolates from Java were clustered in a different group. This group, together with the isolate with distinct position and the other group that were dominated by isolates from Sumatra, were distinct from B. japonicum USDA 110. Therefore it is tempting to speculate that they represent indigenous soybean rhizobial strains. Based on complete sequencing of the amplified 16S rDNA of 21 selected isolates, these isolates could be divided into three groups consisting of twelve Bradyrhizobium elkanii, eight Bradyrizobium japonicum and one Sinorhizobium fredii. Most of the B. elkanii strains were isolated from acid soils at Sitiung, West-Sumatra, while only two isolates were obtained from Java. Four isolates from Java, two isolates  from Sitiung, and two isolates from Bukit Tinggi were identified as B. japonicum. One isolate from Java with a distinct position on the ARDRA was identified as S. fredii.